Evaluation for yield and quality of oil from seven Ricinus communis varieties. - Rivera-Brenes, Paola Andrea (2015)
The objective of this work was to evaluate the yield and quality of oil from seven Ricinus communis varieties. The morphological properties (height of plant, productive branches, length of clusters), yield of seed, and oil quality. The evaluation was conducted at the Fabio Baudrit Moreno Experimental Station of the University of Costa Rica, Alajuela, Costa Rica, from September 2013 to April 2014. A randomized complete block design with a density of 5000 plants/ha was used for the evaluation. The varieties evaluated were ColBio RH 171,09, ColBio HR 205, ColBio HR 268, ColBioHR 157, 401, and NIC. The parameters evaluated showed significant difference (a<0.05). The seven varieties constituted all medium-sized plants. The average was four productive branches for all varieties. ColBio HR 268, ColBio HR 205, and ColBio HR 171 obtained the longer cluster. Stem diameter showed an average between 3 and 4 cm for the seven treatments. In relation toseed yield, variety NIC had the lowest value (860 kg/ha), while ColBio HR 171, 09, ColBio HR 205, and 268 had the highest yield with an average of 2377kg/ha. Oil content was higher for treatments 401 (88%) and ColBio HR 171 (87%). The array 09 showed the highest content of ricinoleic acid (80%), followed by ColBio HR 268 (69%) placing both also among the varieties with higer seed yield, but with lower oil content.